Contrast Sensitivity Is Associated With Chorioretinal Thickness and Vascular Density of Eyes in Simple Early-Stage High Myopia - Liu, Xinting; Wang, Yanli; Ying, Xiaoxiao; Zhang, Fen; Huang, Jing; Yu, Hang; Wang, Qian; Zheng, Miaoran; Hou, Fang; Lesmes, Luis; Lu, Zhong-Lin; Lu, Fan; et al. (Frontiers in Medicine, 2022)
Objective: To evaluate the contrast sensitivity function (CSF) , the chorioretinal thickness and vascular density of eyes as well as their relationships in subjects with simple early-stage high myopia. Methods: Eighty-one young subjects were enrolled in this study. They were categorized into the simple high myopia group (sHM, n = 51) and the low-moderate myopia group (control group, n = 30). Monocular CSF under best correction was measured with the qCSF method. Retinal superficial and deep vascular density, inner and outer retinal thickness and choroidal thickness were measured using optical coherence tomography angiography. Results: The area under logCSF (AULCSF) and the cut-off spatial frequency (Cutoff SF) of the sHM group were significantly reduced compared to the control group (P = 0.003 and P < 0.001, respectively). The parafoveal and perifoveal retinal thickness, deep vascular density and choroidal thickness were also significantly reduced in the sHM group (all P < 0.05). Multiple regression analysis revealed that AULCSF was significantly correlated with retinal deep vascular density, outer retinal thickness in the parafoveal and perifoveal areas (All P＜0.05). Conclusion: Compared to low to moderate myopic eyes, patients with simple high myopia have thinner retinal and choroidal thickness, lower retinal vascular density, and reduced contrast sensitivity. Moreover, the CSF was correlated with the measures of chorioretinal structure and vasculature. The results suggest that the CSF is a sensitive functional endpoint in simple early-stage high myopia.